Pattern reconfigurable dielectric resonator antenna based on phased array switches - Dheyaa Khaleel, Aymen; Fais Mansor, Mohd; Misran, Norbahiah; Tariqul Islam, Mohammad (International Journal of Engineering and Technology, 2018)
This study examines a cuboid dielectric resonator antenna with partial ground plane. The dielectric resonator of the antenna is designed with high permittivity, É›r=30. The dimension used to design this cuboid dielectric resonator antenna was based on the dielectric waveguide model (DWM). Meanwhile, the feeding structure depends on the microstrip feed line that resides above the FR4 substrate. The significance of this study is to obtain a reconfigurable radiation pattern. Switches were used to operate the two array elements with phased control in order to obtain reconfigurable pattern, by controlling the switches, the results produced three different radiation patterns at 2.6 GHz with total efficiency 88%. Hence, this proposed antenna can be used for Long Term Evolution (LTE) of band 7 and band 38 with an impedance bandwidth of more than 200 MHz. This study was implemented in a CST Microwave Studio.Â